Optimization of Vitrification Protocols for Feline Epididymal Spermatozoa: Impact on Post-Warming Sperm Quality and Fertilizing Potential - Wirakan Kallayanathum; Larindhorn Udomthanaisit; Theerawat Tharasanit (Animals, 2025)
Cryopreservation is a powerful tool for genetic preservation, assisted reproduction, and the conservation of valuable species [...]